Working with oral history - the narrative of a talented young man in the middle of the northeastern caatinga/ Trabalhando com história oral - a narrativa de um jovem talentoso em meio a caatinga nordestina - Lúcio Silva dos Santos; Natália Moura Borges (Universidade Estadual de Alagoas, 2020)
This work presents fragments of the life story of a young man who was created in the middle of the northeastern caatinga, in a land settlement called Florestan Fernandes, located in Canindé de São Francisco - SE. Using the Oral History research methodology, which seeks to hear the voices of different subjects and reconstruct their memories, seeking to insert their life experiences in the official history. By listening to the young Geovanio Darlan, 22, engaged in social and economic development projects, aimed at the population of the settlements in this region, it was possible to understand how people's lives work in a space of land originated from the expropriation movement, such as the school, and more specifically the teaching of history, can and should be more incisive in contributing to the strengthening of the local identity and to the citizen formation of individuals.